ANALISIS “KELUARGAKU UNIK” BUKU BAHASA INDONESIA SISWA KELAS II BERBASIS KELAYAKAN BUKU BSNP - Mukharomah, Amelia Rizki; Purwati, Panca Dewi; Febriyanti, Melati Candra; Widitiana, Kurnia Fitri; Hasna, Fatimatul; Saputra, Aditya Ahmad (Jurnal PENEROKA: Kajian Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to analyze the feasibility of “Keluargaku Unik” Indonesian Language book for Elementary School Class II Chapter 4 based on four aspects of book feasibility according to the National Education Standards Agency (BSNP), namely content, language, presentation, and graphical feasibility. This research focuses on analyzing the Indonesian language student book for grade II Chapter 4 and does not cover other chapters in the book. The method used in this research is descriptive qualitative. The research data model consists of reading text, illustrations, and the physical form of the book. The results showed that in general the book had fulfilled the eligibility aspects of content and presentation with appropriate (S) and interesting (M) qualifications. However, language feasibility, especially in the use of spelling, still found some violations such as the use of capital letters and punctuation marks that are not in accordance with the rules of Refined Spelling (EYD). Meanwhile, in the aspect of graphics, the book is considered appropriate (T) although there are still some discrepancies in the placement of illustrations. These findings have an important impact on teachers, schools, and book writers in improving the quality of textbooks in accordance with BSNP standards and the use of good and correct EYD.